1998
DOI: 10.1002/pro.5560070501
|View full text |Cite
|
Sign up to set email alerts
|

Refolding rate of stability‐enhanced cytochrome c is independent of thermodynamic driving force

Abstract: N52I iso-2 cytochrome c is a variant of yeast iso-2 cytochrome c in which asparagine substitutes for isoleucine 52 in an alpha helical segment composed of residues 49-56. The N52I substitution results in a significant increase in both stability and cooperativity of equilibrium unfolding, and acts as a "global suppressor" of destabilizing mutations. The equilibrium m-value for denaturant-induced unfolding of N52I iso-2 increases by 3096, a surprisingly large amount for a single residue substitution. The folding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The most frequently isolated group of second site suppressors were global suppressors at positions 163, 166, and 170 of the coat protein (1). Global suppressors have been identified in other proteins (43)(44)(45). For example, the global suppressors of the tsf mutants in P22 tailspike protein have been shown to alleviate folding defects by decreasing the rate of aggregation through stabilization of a folding intermediate (17, 46 -48).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently isolated group of second site suppressors were global suppressors at positions 163, 166, and 170 of the coat protein (1). Global suppressors have been identified in other proteins (43)(44)(45). For example, the global suppressors of the tsf mutants in P22 tailspike protein have been shown to alleviate folding defects by decreasing the rate of aggregation through stabilization of a folding intermediate (17, 46 -48).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this observation, it has been predicted that residues involved in the folding nuclei of proteins may be conserved across naturally occurring homologous families, or exhibit intra-family conservation across superfamilies, including those of CI-2 (Shaknovich et al, 1996), cytochrome c (Ptitsyn, 1998), ubiquitin (Michnick & Shakhnovich, 1998), CheY (Mirny et al, 1998), ADAh2 (Mirny & Shakhnovich, 1999) and CD2 (Mirny & Shakhnovich, 1999). Only extremely limited mutagenesis/kinetics studies (<10 % of positions characterized) have been reported for cytochrome c (Colo'n et al, 1996;McGee & Nall, 1998), ubiquitin (Khorasanizadeh et al, 1996) or CD2 (Lorch et al, 1999), thus the conservation of kinetically signi®cant residues in these proteins is dif®cult to address at this time. As indicated above, however, we observe no statistically signi®cant evidence in support of the suggestion that residues forming the folding nucleus of CI-2 are highly conserved (Shaknovich et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Measured values of DG ‡ 0T are calculated from "measured" k f or k u using Equation 3~Materials and methods!. Nall, 1997;McGee & Nall, 1998!, suggesting that an analogous submillisecond phase should be observed by temperature jumps of iso-2. There are no faster phases observed by 287 nm absorbance.…”
Section: Burst Phases and Two-state Models Of Foldingmentioning
confidence: 99%